Green strategic intent, artificial intelligence capability and behavioral dynamics of achieving circular economy goals in the public sector - Zahoor, Nadia; Usman, Muhammad; Khalid, Adeel; Aboelmaged, Mohamed Gamal; Yasin, Naveed (Elsevier, 2025)
This study investigates the role of green strategic intent in facilitating the adoption of circular economy practices within public sector organizations. Using the dynamic capability view, we proposed that green strategic intent leads to circular economy practices. We also proposed that artificial intelligence (AI) capability and green learning ambidexterity act as significant underlying mechanisms and leader boundary-spanning behavior as a moderator. Data were collected from 228 managers of various public sector departments in United Arab Emirates (UAE) using a time-lagged design. Our results supported that there is a positive relationship between green strategic intent and circular economy practices. Further, green strategic intent positively influences circular economy practices through AI capability and green learning ambidexterity that act as serial mediators of the green strategic intent-circular economy practices link. Finally, leader boundary-spanning behavior significantly moderates the effects of green strategic intent on AI capability. Our findings offer important insights that can enable public sector organizations to implement circular economy practices.
Keywords: Green strategic intent; AI capability; Green learning ambidexterity; Leader boundary-spanning behavior; Circular economy practices